The Influence of Product Diversification and Brand Associations on Buying Interest - Ricardo Albert; Thomas Sumarsan Goh; Errie Margery; Syawaluddin Syawaluddin (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2022)
During the Covid-19 period, the demand for goods decreased so management must be able to achieve the company's target by increasing consumer buying interest. The purpose of this study is to determine and analyze the influence of Product Diversification and Brand Associations on Buying Interest at PT. Arinvi Mitra Lestari. The sampling technique used a simple random sampling method. The samples used in this study are: the company’s customers, amounting to 92 people. The data analysis method used multiple linear regression analysis. In conclusion, Product Diversification and Brand Associations simultaneously have a positive and significant effect on Buying Interest of PT. Arinvi Mitra Lestari, Deli Serdang. Partially, Product Diversification has a positive and significant effect on the Buying Interest of PT. Arinvi Mitra Lestari, Deli Serdang. Partially, the Brand Association has a positive and significant effect on Buying Interest of PT. Arinvi Mitra Lestari, Deli Serdang. The magnitude of the coefficient of determination can be seen from the Adjusted R Square value of 0.526 which means that Product Diversification and Brand Associations can explain the Buying Interest of 52.6% and the remaining 47.4% is influenced by other variables outside of this study such as brand equity and so on.